The use of computer for geometrical and technological parameters projection of the bevel gears - Vasić, Siniša; Bogičević, Milomir (Journal of Production Engineering, 1986)
In the paper a computer procedure of geometrical and technological parameters projection of the bevel gears is described according to methodes KONVOID, HARBEK and KURVEX. Due to this projection the programing package for automatical projection of geometry of bevel gears known and unknown (reconstruction) and for creating a card for machine adjustment, has been developed.